Peningkatan Kesehatan Reproduksi Remaja melalui Posyandu Remaja Pashmina pada Era New Normal Covid -19 - Maslikhah Maslikhah; Hilda Prajayanti; Ni'matul Ulya; Ida Baroroh (LPPM Akbid Harapan Ibu Pekalongan, 2021)
Adolescence is a period of storm and stress, because adolescents experience many challenges both from themselves (biopsychosocial factors) and the environment (environmental factors). If adolescents do not have the ability to face these challenges, they can end up with complex health problems as a result of their risky behavior. The establishment of the Youth Posyandu is expected to be a forum to facilitate adolescents in understanding adolescent health problems, find alternative solutions to problems, form youth support groups, expand the reach of the PKPR Health Center, especially for regional youth who have limited access. The purpose of this community service is to provide health education about Adolescent Reproductive Health through the “Pashmina” Youth Posyandu in the New Normal Covid 19 Era. The health education methods carried out are (1) Socialization and Licensing, (2) Affirmation and Pre Test (3) Conducting Health education on Adolescent Reproductive Health. (4) Evaluation of the results of health education activities with Post Test. The results of the activity are expected to increase and understand Adolescent Reproductive Health as indicated by an increase in adolescent reproductive health from the results of the Pre Test (before Health Education) and Post Test Results (after health education).